A review of railway feeding infrastructures: Mathematical models for planning and operation - Arboleya, Pablo; Mayet, Clement; Mohamed, Bassam; Aguado-Sánchez, José Antonio; De-la-Torre-Fazio, Sebastián Bienvenido (Elsevier, 2020)
In this paper, the authors review the mathematical models, simulation and analysis techniques and energy management systems proposed for railway power supply systems. The authors review both AC and DC railway feeding systems making special emphasis in those that consider new technologies like on-board or wayside energy storage, integration of renewable energies in the traction networks or the use of power electronic devices to increase the efficiency and controllability of the networks. The paper is divided in two main blocks studying DC and AC systems. In both parts, a review of the main simulation tools and models is presented but also a detailed list of specific cases of use of such techniques.
Keywords: Transporte ferroviario - Abastecimiento de energía; Electrical railways; DC railways; AC railways